Satellite-to-ground quantum key distribution - Liao, Sheng-Kai; Cai, Wen-Qi; Liu, Wei-Yue; Zhang, Liang; Li, Yang; Ren, Ji-Gang; Yin, Juan; Shen, Qi; Cao, Yuan; Li, Zheng-Ping; Li, Feng-Zhi; Chen, Xia-Wei; et al. (Nature (London), 2017)
Quantum key distribution (QKD) uses individual light quanta in quantum superposition states to guarantee unconditional communication security between distant parties. However, the distance over which QKD is achievable has been limited to a few hundred kilometres, owing to the channel loss that occurs when using optical fibres or terrestrial free space that exponentially reduces the photon transmission rate. Satellite-based QKD has the potential to help to establish a global-scale quantum network, owing to the negligible photon loss and decoherence experienced in empty space. Here we report the development and launch of a low-Earth-orbit satellite for implementing decoy-state QKD—a form of QKD that uses weak coherent pulses at high channel loss and is secure because photon-number-splitting eavesdropping can be detected. We achieve a kilohertz key rate from the satellite to the ground over a distance of up to 1,200 kilometres. This key rate is around 20 orders of magnitudes greater than that expected using an optical fibre of the same length. The establishment of a reliable and efficient space-to-ground link for quantum-state transmission paves the way to global-scale quantum networks. Decoy-state quantum key distribution from a satellite to a ground station is achieved with much greater efficiency than is possible over the same distance using optical fibres. Quantum security in orbit The laws of quantum physics give rise to protocols for ultra-secure cryptography and quantum communications. However, to be useful in a global network, these protocols will have to function with satellites. Extending existing protocols to such long distances poses a tremendous experimental challenge. Researchers led by Jian-Wei Pan present a pair of papers in this issue that take steps toward a global quantum network, using the low-Earth-orbit satellite Micius. They demonstrate satellite-to-ground quantum key distribution, an integral part of quantum cryptosystems, at kilohertz rates over 1,200 kilometres, and report quantum teleportation of a single-photon qubit over 1,400 kilometres. Quantum teleportation is the transfer of the exact state of a quantum object from one place to another, without physical travelling of the object itself, and is a central process in many quantum communication protocols. These two experiments suggest that Micius could become the first component in a global quantum internet.